Knowledge, contact and stigma of mental illness: Comparing three stakeholder groups in Hong Kong. (March 2022) - Ran, Mao-Sheng; Peng, Man-Man; Yau, Yuen Yum; Zhang, Tian-Ming; Li, Xu-Hong; Wong, Irene Yin Ling; Ng, Siuman; Thornicroft, Graham; Chan, Cecilia Lai-Wan; Lu, Lin
Background: It remains unknown what the impacts of multiple dimensions of contact (e.g. level, quantity and quality) are on the stigma of mental illness. Aims: To explore the relationship between the multiple dimensions of contact and stigma of mental illness among family members (FM), mental health workers (MHW) and community residents (CR) in Hong Kong. Methods: The stigma, contact and knowledge were measured in FM, MHW and CR in Hong Kong. Multiple regression analyses were used. Results: MHW ( n = 141) had higher knowledge, more contact and lower stigma of mental illness than CR ( n = 95) or FM ( n = 62). Knowledge and contact quality were significantly associated with lower stigma of mental illness in the three groups. However, contact level and contact quantity were not significantly associated with most stigma components. The contact level was positively associated with stigma of mental illness among FM and CR. Conclusions: The results of this study highlight the differences in knowledge, contact and stigma of mental illness among different stakeholder groups. This study suggests that positive contact (e.g. equal, supportive, voluntary and pleasant contact) reduces stigma of mental illness, while negative contact (e.g. unfriendly, unsupportive, unpleasant contact) may increase stigma. The Enhancing Contact Model (ECM) should be tested in future anti-stigma interventions.